Case report: A second case of cerebral cavernous malformation after high-dose chemotherapy for medulloblastoma - Pionelli, Maria Grazia; Mazio, Federica; Errico, Maria Elena; Russo, Carmela; Cristofano, Adriana; Covelli, Eugenio Maria; Donofrio, Vittoria; Capasso, Maria; Capozza, Michele Antonio; De Gregorio, Fabiola; Ruotolo, Serena; Abate, Massimo Eraldo; et al. (Frontiers in Oncology, 2024)
The development of cerebral cavernous malformations (CCMs) is a well-recognized sequela of irradiation to the brain in pediatric tumors, particularly in medulloblastoma, glioma, and acute lymphoblastic leukaemia. So far, only one case of cerebral cavernoma after chemotherapy with autologous hematopoietic stem cell transplantation (HSCT) has been described. We describe a case of a patient with medulloblastoma aged 18 months at the time of oncological diagnosis who was treated with high-dose chemotherapy followed by HSCT and who developed CCM two years later. The patient was not treated for vascular malformation since he remained asymptomatic until now and is regularly followed with neuro-radiological check-ups. This represents the second case of acquired cavernoma developed in a patient who has not received radiation therapy.